Non‐alcoholic fatty liver disease satisfactorily treated with traditional Japanese kampo medicine. Issue 1 (3rd October 2017) - Shimada, Yutaka; Fujimoto, Makoto; Nogami, Tatsuya; Watari, Hidetoshi; Kitahara, Hideyuki; Misawa, Hiroki; Kimbara, Yoshiyuki
ABSTRACT: Case: An obese 17‐year‐old male patient with right hemiparesis secondary to cerebral infarction presented for kampo treatment. The hemiparesis and resultant lack of exercise had led to an increase in bodyweight. Serum alanine aminotransferase (ALT) was elevated and abdominal ultrasound identified fatty liver. The patient was diagnosed with non‐alcoholic fatty liver disease (NAFLD). Aspirin and tocopherol acetate (vitamin E), previously prescribed, were continued, and kampo medicines were prescribed. Outcome: Two years and 6 months after the initial visit, we prescribed keishikashakuyakuto ( Gui Zhi Jia Shao Yao Tang ) extract, in addition to keishibukuryogan ( Gui Zhi Fu Ling Wan ) extract. Thereafter, serum ALT gradually decreased, despite no significant change in bodyweight or blood platelet count. Conclusion: Kampo medicine may be effective for the treatment of NAFLD.